2020
DOI: 10.1080/10438599.2020.1792604
|View full text |Cite
|
Sign up to set email alerts
|

A dose–response evaluation of a regional R&D subsidies policy

Abstract: This paper evaluates the effects of a regional R&D policy in the Italian province of Trento from 2002 to 2007, an ideal testing ground for the role of local government and the effectiveness of an R&D place-based policy. Exploiting a unique database and using a counterfactual dose-response regression model, we perform an evaluation exercise of policy targets concerning employment, fixed and intangible assets.We find that two years after the award date, there exists a range of subsidy doses that is effective in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Although there are many studies examining the impact of EU subsidies on SMEs, there are still very few that consider the intensity of support, the dose. We have found only four: Cerulli et al, 2020;Marino et al, 2016;Bondonio and Greenbaum, 2014;Ginevičius et al, 2007). Moreover, most of the studies focus on specific programmes and usually on short-term effects.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Although there are many studies examining the impact of EU subsidies on SMEs, there are still very few that consider the intensity of support, the dose. We have found only four: Cerulli et al, 2020;Marino et al, 2016;Bondonio and Greenbaum, 2014;Ginevičius et al, 2007). Moreover, most of the studies focus on specific programmes and usually on short-term effects.…”
Section: Discussionmentioning
confidence: 59%
“…So far, only several studies have been carried out that reflected the support dose of EU funding. Research from the Italian province of Trento (Cerulli et al, 2020) found positive effects of EU subsidies (intermediate support doses) on employment, labour quality, and growth of intangible assets, but also showed inefficiency of very small and very large projects. French evaluation of a regional research and development subsidy policy pointed to an increase in private research and development spending with large subsidies, but revealed a low impact with small subsidies (Marino et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the benets of these additional subsidies may be more persistent, as they may not only ease the immediate realization of the project, but also favor R&D increases and upskilling (Mariani & Mealli, 2018;Cerulli et al, 2020). This could be crucial in order to increase the absorptive capacity of small rms, especially those located in the less innovative regions.…”
Section: National Estimatesmentioning
confidence: 99%
“…Governments in many countries provide firms with public financial support for their research and innovation (R&I) activities (Link and Scott 2013;OECD 2023). Subsidising firm-level R&I can generate socio-economic returns, including improved economic performance, and high-quality employment (Choi and Lee 2021;Cerulli et al 2022). Academics and policymakers increasingly recognise that such returns are more likely to arise when public financial support for R&I results in radical innovation in firms (Beck et al 2016;Laplane and Mazzucato 2020;OECD 2021).…”
Section: Introductionmentioning
confidence: 99%
“…There is also a risk of deadweight spending effects, as such firms may use public financial support to carry out R&I activities that they would have carried out anyway (Lenihan 2004;Pereira and Suárez 2018;Mina et al 2021). Investigating whether public financial support for R&I results in radical innovation when focused on these two groups of firms is thus vital, as it can usefully inform a more impactful allocation of public financial support for R&I (Fiorentin et al 2019;Berrutti and Bianchi 2020;Cerulli et al 2022).…”
Section: Introductionmentioning
confidence: 99%